Fixed Point Results of Locally Contractive Mappings in Ordered Quasi-Partial Metric Spaces - Abdullah Shoaib; Muhammad Arshad; Jamshaid Ahmad (The Scientific World Journal)
Fixed point results for a self-map satisfying locally contractive conditions on a closed ball in an ordered 0-complete quasi-partial metric space have been established. Instead of monotone mapping, the notion of dominated mappings is applied. We have used weaker metric, weaker contractive conditions, and weaker restrictions to obtain unique fixed points. An example is given which shows that how this result can be used when the corresponding results cannot. Our results generalize, extend, and improve several well-known conventional results.